"What Is Security?" Conference with Keynote Speaker Richard Lehman - Watkins, Howard::::::::: (1987)
Women's International League for Peace and Freedom workshop; Steve Malm at chalkboard; Barbara Gaines seated; Women's International League for Peace and Freedom bus placard on board